Effects of chronobiological feeding model on sleep and physiological parameters of preterm infants: A randomized controlled trial - Temizsoy, Ebru; Bozkurt, Neslihan; Ovali, Fahri; Uysal, Gulzade; Sursal, Alihan (Elsevier, 2026)
Aligning feeding schedules with biological rhythms in chrononutrition could aid circadian rhythm development. The objective of this research was to assess how a chronobiological feeding model influences sleep and physiological outcomes in preterm infants. This randomized controlled trial was carried out in a tertiary-level neonatal intensive care unit from April 2023 to March 2024. Sixty preterm infants were randomly assigned either to the intervention group (n = 30) or the control group (n = 30). In the intervention group, milk expressed at specific times of the day was administered correspondingly. Data on demographic features, sleep duration, crying time, and physiological parameters were collected using a structured monitoring form. The mean birth weight did not differ significantly between groups (chrononutrition = 1985.4 f 731.8 g; control = 1946.4 f 545.7 g; p = 0.815). No differences were found in demographic characteristics (p > 0.05). Oral feeding initiation (OFI) quiet sleep duration was similar between groups (30.6 f 33.3 vs. 25.7 f 20.9 min; p = 0.497). At the time of discharge, infants in the chrononutrition group had a significantly longer quiet sleep duration (79.5 f 46.4 vs. 47.9 f 20 min; p = 0.001) with higher increase over time (48.9 f 35.3 vs. 22.7 f 25.6 min; p = 0.002). There were no statistically significant differences between the groups in terms of crying duration or physiological parameters (p > 0.05). Chronobiology-based feeding improved sleep among preterm infants without altering physiological balance. Further investigation should assess its lasting impact on circadian and developmental processes.
Keywords: Chrononutrition; Preterm infants; Sleep; Physiological parameters; Circadian rhythm